General banking operation of Mercantile Bank Limited (MBL), Suaganj bazar branch,Comilla - Alam, Md. Mohsin (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2016.